Teacher's Questioning Strategies during the Classroom Interaction at Islamic Senior High School - Putri, Desi Yulia; Reflinda, Reflinda (FOSTER: Journal of English Language Teaching, 2021)
There were several students’ problems that the writer found at Private Islamic Senior High Schools (MAS) including in MAS AsySyarif Koto Laweh Tilatang Kamang. First, some students are often silent in English class. Second, some students find it difficult to understand the learning material. The last the teacher ignores the differences in students' abilities. This research aims to determine the type of questioning strategy and how to apply the questioning strategy in classroom interaction. This research is qualitative descriptive. The informant of this research was an English teacher at MAS AsySyarif Koto LawehTilatangKamang. The data were obtained through observation and interviews. This research found 6 types of Questioning Strategies used by the teacher, there were Knowledge questions, Comprehension questions, Application questions, Analysis questions, Synthesis questions, Evaluation questions. And found 3 to apply questioning strategy there were, questioning at the beginning, Questioning at the middle of the class, and Questioning at the end.